2008
DOI: 10.1089/tea.2007.0249
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Improve Cellular Content for Corporal Tissue Engineering

Abstract: We have previously shown that penile corporal structures engineered using autologous cells are able to achieve erection, penetration, and ejaculation. However, fully functional corpora could not be engineered because of the limited cellular content present within the corporal tissue construct. In this study, we investigated whether a dynamic seeding approach would improve cellularity within the corporal tissue construct and thereby restore normal erectile function. Corporal cells were either statically or dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Thus, in this study, we engineered entire segments of the pendular neocorpora, using autologous cells and maximized the SMC content. A multistep dynamic/ static seeding procedure was used (14). With this method, we were able to seed 5.9 times as many SMC than our prior experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in this study, we engineered entire segments of the pendular neocorpora, using autologous cells and maximized the SMC content. A multistep dynamic/ static seeding procedure was used (14). With this method, we were able to seed 5.9 times as many SMC than our prior experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A multistep static/dynamic seeding method was used to improve cell attachment and homogeneity on the matrices (14). On the first seeding day, approximately 60 × 10 6 SMC/mL were injected into the decellularized corporal tissue matrix at multiple sites using a 22-gauge needle, and then the construct was placed in culture for 24 h in DMEM supplemented with 10% FBS and 1% penicillin-streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group also reported that cultured human corporal smooth muscle and endothelial cells seeded on biodegradable acellular matrix-derived donor rabbit corpora exhibited much better functional and morphologic results compared to unseeded control animals due to the ability to form well-vascularized corporal tissues in vivo [85]. Furthermore, dynamically seeded corporal cells on acellular corporal tissue matrices and maintained in a bioreactor system resulted in improved formation of normal corpora (71% vs. 39% in statically seeded matrices) due to more dynamic cell attachment [86]. In addition to the engineered neo-corpora, cavernous nerve-excised rats, when implanted with acellular nerve grafts, demonstrated adequate ICP at 3 months and the presence of host-cell Adipose-derived stem cell Hypercholesterolemic rat ↑ ICP, nNOS, smooth muscle, and endothelial markers Huang et al [79] Adipose-derived stem cell CNI rat ↑ ICP, nNOS, and SMC preservation cGMP-cyclic guanosine monophosphate; CNI-cavernous nerve injury; eNOS-endothelial nitric oxide synthase; ICP-intracavernosal pressure; nNOS-neuronal nitric oxide synthase; NOS-nitric oxide synthase; SMC-smooth muscle cell infiltration within the nerve sheath [87].…”
Section: Tissue Engineeringmentioning
confidence: 94%
“…Biodegradable scaffolds have been used as cell delivery systems in many tissue-engineering studies. Recently, a scaffoldless cavernous-tissue-engineering method has been described [84]. Here, rat adipose tissuederived stem cells were isolated and differentiated into SMCs and used with ECs to construct cavernous tissue.…”
Section: Penile Reconstructionmentioning
confidence: 99%